2017
DOI: 10.1016/j.contraception.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum care and contraception provided to women with gestational and preconception diabetes in California's Medicaid program

Abstract: Objectives: To compare rates of postpartum care and contraception provided to women with gestational or preconception diabetes mellitus to women with no known diabetes mellitus. Methods: A retrospective cohort study of 199,860 women aged 15-44 years who were continuously enrolled in California's Medicaid program, Medi-Cal, from 43 days prior to 99 days after delivering in 2012. Claims for postpartum clinic visits and contraceptive supplies were compared for 11,494 mothers with preconception diabetes, 17,970 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
(27 reference statements)
0
19
0
Order By: Relevance
“…More research is needed to understand how women want family planning and preconception care incorporated into diabetes management. Future research should continue to build on the emerging evidence that the postpartum period may be a particularly promising time for innovations in family planning service delivery …”
Section: Discussionmentioning
confidence: 99%
“…More research is needed to understand how women want family planning and preconception care incorporated into diabetes management. Future research should continue to build on the emerging evidence that the postpartum period may be a particularly promising time for innovations in family planning service delivery …”
Section: Discussionmentioning
confidence: 99%
“…Then, we required additional continuous enrollment for the measure‐specified time frame to identify the second element (eg, glucose test procedures). We referred to published articles, guidelines, and online medical coding tools to identify relevant diagnosis and procedure codes, as well as medications for specified conditions . An obstetrician on the study team provided feedback to establish face validity of the selected codes and time frames for codependent claims.…”
Section: Methodsmentioning
confidence: 99%
“…21 To optimize subsequent pregnancy outcomes, contraception and family planning are key; however, previous research indicates women with pregestational and gestational diabetes may be less likely than women without diabetes to use effective contraception. 22,23 One recent national survey indicated that 20 to 40% of pregnancies following the longest interpregnancy intervals were unintended. 24 Unintended pregnancy among women with a history of gestational diabetes may be particularly important.…”
Section: Commentmentioning
confidence: 99%